2016
DOI: 10.1038/srep26618
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based site-directed photo-crosslinking analyses of multimeric cell-adhesive interactions of voltage-gated sodium channel β subunits

Abstract: The β1, β2, and β4 subunits of voltage-gated sodium channels reportedly function as cell adhesion molecules. The present crystallographic analysis of the β4 extracellular domain revealed an antiparallel arrangement of the β4 molecules in the crystal lattice. The interface between the two antiparallel β4 molecules is asymmetric, and results in a multimeric assembly. Structure-based mutagenesis and site-directed photo-crosslinking analyses of the β4-mediated cell-cell adhesion revealed that the interface between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Cis ‐interactions have also been characterized for the Nav channel β4‐subunit, independently of its binding to Nav channels. In this case, the cis‐interactions between β4‐subunits facilitate trans‐cell adhesion behavior . The β3‐subunit has also been shown to promote trans ‐cell adhesion, at least under conditions of high expression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cis ‐interactions have also been characterized for the Nav channel β4‐subunit, independently of its binding to Nav channels. In this case, the cis‐interactions between β4‐subunits facilitate trans‐cell adhesion behavior . The β3‐subunit has also been shown to promote trans ‐cell adhesion, at least under conditions of high expression .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the cis-interactions between β4-subunits facilitate trans-cell adhesion behavior. [20][21][22] The β3-subunit has also been shown to promote trans-cell adhesion, at least under conditions of high expression. 19 Hence, the ability of β3subunits to homo-trimerize may reflect a more general tendency of Nav channel β-subunits to self-assemble, at least under some in vivo conditions-for example, in the absence of Nav α-subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The function of β4 in cell adhesion remains more poorly understood (Brackenbury and Isom 2011). Insights from crystallographic, mutagenic, and photo-crosslinking studies have revealed the structural importance of an antiparallel interface between β4 subunits in trans homophilic adhesion (Shimizu et al 2016). Recent evidence shows that β4 Ig domains interact in a parallel manner involving a disulfide bond between cysteine 58 and hydrophobic and hydrogen bonding interactions between residues 30 through 35.…”
Section: The Basics Of the Voltage-gated Sodium Channel β Subunitsmentioning
confidence: 99%
“…Recent advances in cryo-EM have allowed reconstructions of Na V 1.4 from electric eels (3) and humans (4) and an Na v from the American cockroach (5). In addition, high-resolution crystal structures have been reported for the Ig domains of mammalian Na V β2, β3, and β4 (6)(7)(8)(9). Despite these advances, the bulk of the cytosolic region appeared invisible in the cryo-EM reconstructions, suggesting inherent flexibility relative to the TM region.…”
mentioning
confidence: 99%